Neutrophil-induced ferroptosis promotes tumor necrosis in glioblastoma progression - Patricia P. Yee (Nature Portfolio, 2020)
Tumour necrosis is associated with tumour aggressiveness and poor outcomes in patients with glioblastomas, but the underlying mechanisms remain poorly understood. Here, the authors show that in a xenograft mouse model of glioblastoma, tumour-infiltrating neutrophils amplify necrosis by promoting myeloperoxidase-induced tumour cell ferroptosis.